Results of Simultaneous Bilateral Endoscopic Dacryocystorhinostomy, Duration of Surgery, and Evaluation of Success and Complications - DERİCİOĞLU, VOLKAN (My University, 2022)
Purpose: It was aimed to evaluate the results of simultaneous bilateral endoscopic dacryocystorhinostomy (DCR).Method: Simultaneous bilateral endoscopic DCR was applied to patients with bilateral acquired nasolacrimal duct obstruction who applied to Marmara University, Department of Ophthalmology between 2020-2022. Patients with punctal - canaliculi occlusion and a history of previous DCR were excluded from the study. Only Kerrison punch and curettes were used for bone excision in all cases, and lacrimal intubation was applied to all eyes. History of dacryocystitis, duration of symptoms and surgery, complications, and functional and anatomical success parameters were evaluated.Results: Twenty-four eyes of 12 patients were included in the study. The female ratio was 4/12 (33.3%), and the mean age of the patients was 50.9±9.1 years. Six eyes (25%) had a history of dacryocystitis. The mean time to development of symptoms was 9.21±4.14 months. The mean operation time per eye was 37.08±6.41 (min:25-max:50) minutes. The functional and anatomical success rates at 3 months were 91.7% (n=22) and 95.8% (n=23), respectively; and 6 months success rates were 87.5% (n=21) and 91.7% (n=22), respectively. While no perioperative complication was observed, the hematoma was seen in 4 eyes (16.6%), and intranasal bleeding occurred in 2 eyes (8.3%) postoperatively. In one of the anatomically unsuccessful eyes, the lacrimal intubation tube extruded on the 3rd postoperative day, and another eye had a history of dacryocystitis.Conclusion: Simultaneous endoscopic DCR can be applied as a useful method in bilateral acquired nasolacrimal duct obstructions with its high anatomical and functional success rate, short operation time, and low complication rates.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Göz Hastalıkları ve Cerrahisi; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Eye Diseases and Surgery; Health Sciences; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; OFTALMOLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; OPHTHALMOLOGY; Optometri; Cerrahi; Oftalmoloji; Optometry; Surgery; Ophthalmology